Surface engineering to achieve organic ternary memory with a high device yield and improved performance. Issue 3 (5th January 2017) - Hou, Xiang; Xiao, Xin; Zhou, Qian-Hao; Cheng, Xue-Feng; He, Jing-Hui; Xu, Qing-Feng; Li, Hua; Li, Na-Jun; Chen, Dong-Yun; Lu, Jian-Mei
Abstract : Organic memories fabricated on surface-engineered indium tin oxide show the highest ternary yield (82%) to date and better performance. Abstract : Squaraine molecules deposited on indium tin oxide (ITO) substrates modified with phosphonic acids crystalize more orderly than do those on untreated ITO. The as-fabricated electro-resistive memories show the highest ternary device yield observed to date (82%), a narrower switching voltage distribution, and better retention as well as resistance uniformity.